Pengaruh Job Insecurity Terhadap Turnover Intention: Systematic Literature Review - Tutut Desti Ayuningtyas; Shelly Dyah Aprilia; Fajar Tri Wahyuningsih; Dani Rizana (Journal of Literature Review, 2025)
Rapid changes in the modern business environment have increased job insecurity across various sectors. This phenomenon raises concerns about potential job loss, which may lead to employees’ higher turnover intention. This study aims to systematically review previous research on the influence of job insecurity on turnover intention using the Systematic Literature Review (SLR) method. Articles were collected from Google Scholar and Emerald Insight databases, with publication years ranging from 2019 to 2025. The research process consisted of several stages: literature identification, inclusion and exclusion criteria selection, quality assessment, and narrative data synthesis. The findings indicate that job insecurity has a positive and significant effect on turnover intention. Employees who perceive higher job insecurity tend to experience lower job satisfaction and organizational commitment, resulting in a stronger desire to leave the organization. Furthermore, several studies revealed that mediating variables such as job satisfaction, organizational commitment, and job engagement, as well as moderating variables such as work motivation and perceived organizational support, can weaken the relationship between job insecurity and turnover intention. In conclusion, strengthening job security, providing organizational support, and maintaining employees’ motivation are essential strategies to reduce turnover intention and enhance employee loyalty.